The UK Nationwide Observational Study of Colon Capsule: CAP ACCESS National Audit - Ian Io Lei; Hussain Ibrahim; Rauri Jardine; Waleed Beshyah; Aamerrashad Arefin; Matthew Jarocki; Conor Mcgreevy; Lushen Pillay; Sachin Patel; Tracey Ambler; Giorgi Kiladze; Sujith Sasidharan Nair; et al. (Clinical Medicine, 2025)
Background: Colon capsule endoscopy (CCE) is increasingly used as an alternative to optical endoscopy (OE), particularly in Europe. However, challenges, such as low completion rates, inadequate bowel preparation, high conversion to OE and discrepancies in findings, remain. Accurate polyp size measurement during CCE is crucial to determine the need for further endoscopic procedures. Overestimating polyp size can lead to unnecessary procedures, patient distress and strain on the healthcare system. Objective: This retrospective study analysed real-world data to compare polyp size measurements between CCE, OE and histopathology (HP) and assess the impact on the need for further procedures. Methods: Data from 2,508 participants who underwent CCE from 12 different UK centres were analysed. 4,898 polyps identified via CCE were carefully matched with corresponding OE and HP reports based on specific criteria, such as polyp size, location, morphology, sequence and overall count. Only polyps meeting at least three criteria were paired and included for comparison. Given significant differences in CCE indications and service provision, regional data from Scotland and England were compared to gain insights into practical approaches. Results: Half of all CCE patients required follow-up OE, with 29% undergoing colonoscopy and 21% flexible sigmoidoscopy. Among these, 32% were performed for polypectomy and 18% because eof incomplete CCE. On average, CCE overestimated polyp size by 2.5 mm compared with histopathology and 2.7 mm compared with OE, leading to 17.3% potentially avoidable procedures. Per-polyp sensitivity exceeded 91% across polyp size ≥6 mm, while per-patient sensitivity for detecting lesions requiring OE was 93.8%. The most common reasons for missed polyps >9 mm were incomplete procedures (37%), missed lesions in the ascending colon (19%) and partial cecum visualisation (7%) resulting from rapid capsule transit. Regional comparison showed a higher follow-up rate in NHS Highland, including a significant 8.3% increase in flexible sigmoidoscopies compared with NHS England (p<0.001), likely driven by differing CCE indications and patient selection criteria. The median interval from CCE to OE on the urgent NHS England Tier 1 pathway was 31 days. Conclusion: One in six participants had a further procedure, reflecting the overestimation of polyp size. AI advancement could enhance polyp measurement accuracy and reduce unnecessary procedures while improving the cost-effectiveness of CCE.